Fragmentation, habitat composition and the dispersal/predation balance in interactions between the Mediterranean myrtle and avian frugivores - González-Varo, Juan P. (Ecography, 2010)
Human-induced fragmentation and disturbance of natural habitats can shift abundance and composition of frugivore assemblages, which may alter patterns of frugivory and seed dispersal. However, despite their relevance to the functioning of ecosystems, plant-frugivore interactions in fragmented areas have been to date poorly studied. I investigated spatial variation of avian frugivore assemblages and fruit removal by dispersers and predators from Mediterranean myrtle shrubs (Myrtus communis) in relation to the degree of fragmentation and habitat features of nine woodland patches (72 plants). The study was conducted within the chronically fragmented landscape of the Guadalquivir Valley (SW Spain), characterized by 1% of woodland cover. Results showed that the abundance and composition of the disperser guild was not affected by fragmentation, habitat features or geographical location. However, individual species and groups of resident/migrant birds responded differently: whereas resident dispersers were more abundant in large patches, wintering dispersers were more abundant in fruit-rich patches. Predator abundances were similar between patches, although the guild composition shifted with fragmentation. The proportion of myrtle fruits consumed by dispersers and predators varied greatly between patches, but did not depend on bird abundances. The geographical location of patches determined the presence or absence of interactions between myrtles and seed predators (six predated and three non-predated patches), a fact that greatly influenced fruit dispersal success. Moreover, predation rates were lower (and dispersal rates higher) in large patches with fruit-poor heterospecific environments (i.e. dominated by myrtle). Predator satiation and a higher preference for heterospecific fruits by dispersers may explain these patterns. These results show that 1) the frugivore assemblage in warm Mediterranean lowlands is mostly composed of fragmentation-tolerant species that respond differently to landscape changes; and 2) that the feeding behaviour of both dispersers and predators influenced by local fruit availability may be of great importance for interpreting patterns of frugivory throughout the study area.
Keywords: Dispersers; fragmentation; patches (voyant); predators; seed dispersal